Improvement Energy Consumption in Fault-tolerant Large-Scale Wireless Sensor Networks: DECROP protocol - القبيلي, مثنى; حسن, لميس (Latakia University Journal -Engineering Sciences Series, 2020)
Large scale wireless sensor networks (LS-WSNs) are composed of thousands of sensors, scattered over a wide area, generating a great amount of sensing readings that must be carefully processed to effectively manage the use of available resources. Unlike small scale WSNs, replacing a LS-WSN costs money, time and efforts and in many times the replacement is unfeasible. Thus, the need of robust fault tolerant solutions becomes an obligation in particular in new WSN applications such as military applications, to monitor borders or battle fields, and the underwater surveillance to prevent disasters, monitor pollution, etc. There are several routing protocols, designed for L-WSNs, implement fault tolerance mechanisms to recover it from a failure. DECROP has a simple and efficient structure that makes it desirable as a fast response technique and reduces control messages (overhead). But it suffers from the rapid energy depletion because of its tree structure and irregular clusters. In this research, we propose using the Generic Top-Down cluster and cluster-tree formation (GTC) algorithm in clusters formation phase into DECROP Protocol. The simulation results showed a marked improvement in the performance of the improved protocol in terms of power consumption and network life time while maintaining the basic DECROP features.